Development of a novel patient focussed symptom severity index for use in assessing and treating inflammatory conditions of the lactating breast: a Delphi study. Issue 2 (June 2020) - Cooper, Melinda; Lowe, Helen; McArdle, Adelle
ABSTRACT: Aim: To investigate the content and face validity of a patient-reported outcome measure used by Australian physiotherapists in the assessment of inflammatory conditions of the lactating breast. Methods: Sixty one experts representing 'women who previously had inflammatory conditions of the lactating breast' (48%), 'clinicians' (38%) and 'academics' (8%) interested in women's health and 7% unidentified participants were invited to complete a three round Delphi study. Results: Ninety five percent of participants agreed that overall, the patient-reported outcome measure was appropriate for use in assessing and treating inflammatory conditions of the lactating breast. The item 'impact' was added to ensure the appropriate assessment of functional aspects of daily life. The item terminology used in the patient-reported outcome measure was simplified to 'pain', 'redness', 'hardness/tightness', 'temperature of affected area', 'sickness/wellness' and 'affected area. A clinician script was developed to ensure the patient-reported outcome measure has utility and consistency regardless of the experience of the women presenting with inflammatory conditions of the lactating breast or the clinician. Conclusion: The resultant Breast Inflammatory Symptom Severity Index (BISSI) is a patient-reported outcome measure for use in the diagnosis and monitoring of clinical changes of symptoms associated with inflammatory conditions of the lactating breast including engorgement, blocked ducts and mastitis. It utilizes person-centred language and assesses symptoms considered important to both patient and clinician. The development of the clinician script facilitates utility regardless of the experience of either the woman with the inflammatory condition or the treating clinician.